Does medical training in Thailand prepare doctors for work in community hospitals? An analysis of critical incidents - Dumrongrat Lertrattananon; Wirun Limsawart; Alan Dellow; Helen Pugsley (BMC, 2019)
Abstract Background Compulsory 3-year public service was implemented in 1967 as a measure to tackle the maldistribution of doctors in Thailand. Currently, therefore, most medical graduates work in rural community hospitals for their first jobs. This research explored doctors' perceptions of preparedness for practice using a critical incident technique. Methods A self-administered critical incident questionnaire was developed. Convenient samples were used, i.e. Family Medicine residents at Ramathibodi Hospital who had worked in a community hospital after graduation before returning to residency training. Participants were asked to write about two incidents that had occurred while working in a community hospital, one in which they felt the knowledge and skills obtained in medical school had prepared them for managing the situation effectively and the other in which they felt ill-prepared. Data were thematically analysed. Results Fifty-six critical incidents were reported from 28 participants. There were representatives from both normal and rural tracks of undergraduate training and community hospitals of all sizes and all regions. Doctors felt well-prepared to provide care for patients in emergency situations and as in-patients, but under-prepared for obstetric and paediatric emergencies, out-patient care, and palliative care. Moreover, they felt poorly prepared to deal with difficult patients, hospital administration and quality assurance. Conclusions Long-term solutions are needed to solve the rural doctor shortage. Medical graduates from both normal and rural tracks felt poorly prepared for working effectively in community hospitals. Medical training should prepare doctors for rural work, and they should be supported while in post. Keywords Preparedness for practice, Community hospital, Critical incident, Rural doctor, Rural practice, Undergraduate medical training